Das Siegerland als Beispiel wirtschaftsgeschichtlicher und wirtschaftsgeographischer Harmonie - Fickeler, Paul (ERDKUNDE, 1954)
This paper discusses the historical and geographical aspects of the economy of the Siegerland, one of the most ancient and interesting centres of the iron industry in Middle Europe, and shows the harmony found between nature and the various human activities. Excavations have shown that iron was worked extensively during the La Tene period (500 B. C. — 100 A. D.) (cf. map). To the original location factors, iron ore and charcoal, water power was added and played an important role from the 13 th to the 19 th centuries (cf. map). The great demand for charcoal could only be satisfied by the development of the Haubergwirtsdiaft, a flexible type of landuse where, in a closely regulated manner, the same land was used in succession for oak-birch Niederwald (scrub), and for arable and pasture, thus satisfying the requirements of both industry and agriculture. The Siegerland provides a unique example of this well-balanced form of land use. From about 1860, when charcoal was superseded by hard coal, until about 1900, the oak scrub supplied a considerable boot sole leather tanning industry with tanning bark. When bark was eventually replaced by the development of quick tanning agents, the tanning industry ceased, and the scrub began to revert to a high forest of deciduous trees and firs. Today, about half of the former scrub area has become high forest; a development which has altered the scene most strikingly. Since 1850 the ancient iron ore mines have been replaced by successively deeper workings. Today depths of 1,000 m. are common, while in one case, a depth of 1,303 m. is the greatest yet to be achieved in any iron ore mine. The local iron industry has made important contributions to metal processing techniques. This has resulted in a high degree of concentration of certain specialised branches of processing. Of the present ten German Walzengiefiereien (a certain type of foundry) eight are found in the Siegerland. Their existence has promoted the tin plate rolling industry which specialises in fine tin plates. This in turn has favoured the production of tin plate goods, the local industry accounting for half of the entire German output. These industries are the basis of the Siegerland engineering industry, which produces a wide variety of machines ranging from all types of large equipment down to typewriters, for both domestic and export markets. A synoptic chart in the text shows the logical grouping, the compactness and balanced harmony of the economic structure of the Siegerland and also indicates the historical relationship between the various branches of production and the mutual relationship between the economic structure and the landscape (cf. p. 49).